Pelatihan Digital Marketing Untuk Meningkatkan Digital Literacy Umkm Rusunawa Wonorejo, Surabaya - Lindiawati Lindiawati; Romi Ilham; Heri Supriyanto; Dewi Ayu Wulandari; Yudha Delonix Renzina (-, 2023)
In ‘Rusunawa’ (a rented simple flat which belongs to the Surabaya government, at Wonorejo, Rungkut District, Surabaya) there are about thirty MSMEs (Micro-small-medium entrepreneurs) whose market response is relatively low. This is due to the limited number of the target market mostly ranging from those living in ‘rusunawa’ to relatives and friends contacted through social media. The business owners have not accessed to other customers through optimizing social media uses specifically to offer products and manage orders. Based on problem root, it is necessary to give the MSMEs a training to set up and manage simple application such as WhatsApps Business, Google Business, and Instagram. These applications are popular, potentially easy to learn, set, and apply by MSME owners which are household wives. The training, firstly, was not immediately expected to increase sales, rather to increase their digital literacy first. One big obstacle encountered was that household wives who mostly are above forty years old were not familiar with social media. That’s why there were only limited participants actively implementing the training. They have shown good performance in optimizing social media use falling to the areas of making account of WhatsApp Business, intensively upload content in that business application and Instagram. The training has triggered and improved the participants’ digital literacy.